Form Generator A CAD tool for conceptual design development - Colakoglu, Birgul; Keskin, Gokhan (ECAADE-EDUCATION & RESEARCH COMPUTER AIDED ARCHITECTURAL DESIGN EUROPE, 2010)
This paper presents a new computer-aided design tool named Form Gnerator (FG). It is developed within a visualization software as a scripted utility. It aims to assist designers and students in creating and exploring absract form compositions.
Keywords: Generative design; shape grammars; rule based design; GRAMMARS; Architecture